Pilot-Scale Cultivation of Seaweed (Undaria pinnatifida) Along an Offshore Wind Farm in Southwestern Korea - Dongmun Choi; Hyung-Gon Lee; Yun-Hwan Jung; Dae-Won Lee; Jeonghoon Han; Ji-Yeon Hyeon; Young-Ung Choi (Journal of Marine Science and Engineering, 2025)
Marine environments provide a unique opportunity to blend offshore wind energy production and marine fishery activities as complementary technologies. This study investigated the morphological characteristics (length and weight) and biomass yield of seaweed (Undaria pinnatifida) in a model marine environment with mariculture within an offshore wind farm in southwestern Korea. The mean lengths in the first cultivation trials of U. pinnatifida sporophytes increased from 1.8 ± 0.1 cm in November 2021 to 120–170 cm in March 2022 (density, 39.8 plants m−1; final wet weight, 98.6–249.1 g (mean 146.8 ± 20.4 g, n = 20 ind.); yield 5842 g m−1). Further, for the second cultivation trial, the length of the sporophytes increased from 1.5 ± 0.1 cm in November 2021 to 120–150 cm in April 2022 (density, 49.3 plants m−1; final wet weight, 83.0–251.6 g (mean 155.7 ± 19.0 g; n = 20 ind.); yield, 7676 g m−1), and, owing to the increase in water temperature and light intensity due to seasonal changes around the offshore wind power farm, the second cultivation trials showed signs of chlorosis. Considering the environment, we judged seaweed growth to be normal. Therefore, when applying this model to grow U. pinnatifida, seasonal temperature changes, the purpose of the product, and the nutritional status of the open-sea area should be considered. These results may improve seaweed farming in offshore wind farms in the future.